"Impact of comprehendible learning modes on oral health among visually impaired adults". (17th July 2018) - Vyas, Shaleen; Nagarajappa, Sandesh; Dasar, Pralhad L.; Mishra, Prashant
Abstract: Aim: To assess changes in oral hygiene status, oral health knowledge and behavior among visually impaired individuals using dental health education material transcribed in Braille and Compressed speech. Methodology: A nonrandomized before and after comparison study was conducted among 4 purposively selected institutes for visually impaired in Indore region, Central India. A stratified random sampling was employed to select 144 visually impaired individuals aged 15–35 years. Oral health education (OHE) material was developed in Braille and compressed speech. Participants were intervened using OHE material. A self‐administered Braille transcribed proforma was used to record participants responses on oral health knowledge and behavior at baseline, 1‐week, 1‐month, and 3‐months followed by clinical examination. Descriptive statistics was used for frequencies, mean, and standard deviation of variables. Bivariate regression analysis was performed to assess the effect of independent variables on self‐reported oral health, knowledge score and oral hygiene status. Results: The mean knowledge score of participants in Braille group at 3‐month was significantly higher (11.86 ± 2.41) than in compressed speech group (8.59 ± 2.74). Compressed speech showed significant reduction in mean gingival score (1.02 ± 0.73) at 3‐month ( P ≤ 0.001). Bivariate regression indicated Braille education was significantly effective in improving knowledge (OR: 6.02) and oral hygiene status (OR: 8.24) ( P ≤ 0.001). Conclusion: Braille method of intervention was more effective in improving knowledge scores and oral hygiene status among visually impaired participants.